Pelatihan Pemanfaatan Barang Bekas Sebagai Media Pembelajaran di Taman Kanak-Kanak - M. Dani Wahyudi; Celia Cinantya; Maimunah Maimunah (Carmin: Journal of Community Service, 2021)
The problem that occurs in this community service activity is the use of learning media that is less varied. This is because most teachers are less creative in utilizing the objects around them as innovative learning media. Therefore, the solution used to overcome this problem is to carry out workshops on using used goods as learning media in Kindergarten. This activity aims to provide insight and skills to teachers in partner schools to use used materials around them in interesting learning media. This activity was carried out at the Pembina State Kindergarten, East Banjarmasin District, Banjarmasin City. The method used in this activity is the lecture, demonstration and question and answer method. All teachers in the school participated in this activity. This training activity results in teachers gaining knowledge and skills in utilizing used goods in the surrounding environment in interesting and innovative learning media.